2020
DOI: 10.3390/ani10091573
|View full text |Cite
|
Sign up to set email alerts
|

Factors Informing the Return of Adopted Dogs and Cats to an Animal Shelter

Abstract: Although the adoption rate of dogs and cats from animal shelters has increased, a proportion of animals are returned to the shelter after they are adopted. The purpose of this study was to assess the factors informing the return of 102 dogs to an animal shelter over a four-month period, and the return of 72 cats to an animal shelter over a three-month period. Descriptive statistics revealed dogs are most commonly returned for behavior issues related to aggression (38.2%), and cats are most commonly returned du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 44 publications
2
32
1
1
Order By: Relevance
“…Behavioral issues were a key reason for return of both dogs and cats, which parallels the current body of evidence and affirms the importance of animal behavior in the development of a positive human-animal relationship 8 , 9 , 12 , 18 . Charleston Animal Society provides a multitude of behavioral support services for adopters, although data regarding the utilization of these services was not available.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Behavioral issues were a key reason for return of both dogs and cats, which parallels the current body of evidence and affirms the importance of animal behavior in the development of a positive human-animal relationship 8 , 9 , 12 , 18 . Charleston Animal Society provides a multitude of behavioral support services for adopters, although data regarding the utilization of these services was not available.…”
Section: Discussionsupporting
confidence: 71%
“…Behavioral problems are reported as a key reason for unsuccessful dog adoptions worldwide 6 , 8 , 17 , 18 . A recent study of 102 returned dogs at a shelter in Texas found 56% of dogs were returned due to behavioral issues, 31% were returned for owner-related reasons and 9% were returned for medical needs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations